A Contextual and Adaptive Approach to PAI Learning for 21st Century Education at SMPN 1 Kras, Kediri - Ludviana, Vieke (Ensiklopedia: Jurnal Pendidikan dan Inovasi Pembelajaran Saburai, 2025)
Rapid developments, especially in the digital era and globalization, have had a significant impact on the world of education, including in the learning of Islamic Religious Education (PAI). In junior high schools, such as SMPN 1 Kras Kediri, PAI teachers are faced with the challenge of delivering religious material that is not only informative, but also applicable, relevant, and able to answer real problems faced by students in everyday life. This study aims to analyze the contextual and adaptive approach in PAI learning for today's education at SMPN 1 Kras Kediri. The research approach uses a qualitative descriptive type. Data collection in this study uses interviews, observation and documentation. Data analysis with data condensation flow (data condensation), data presentation (data display), conclusion drawing or verification (conclusion drawing/verification). The results of the study show The implementation of contextual Islamic Religious Education (PAI) at SMP Negeri 1 Kras effectively links Islamic teachings with students’ real-life experiences, enhancing learning relevance, motivation, and holistic outcomes. By integrating Islamic values into social and cultural contexts, students develop cognitive, affective, and behavioral competencies such as honesty, empathy, and responsibility. Teachers act as facilitators, fostering critical, creative, and collaborative thinking aligned with 21st-century skills. The holistic evaluation system through projects, reflective journals, and authentic assessments measures and strengthens the internalization of Islamic values. The practical implications of this research indicate that Islamic Religious Education teachers need to implement contextual learning that links material to students' real experiences and uses authentic evaluation to assess the understanding and internalization of religious values as a whole.